Incorporation of Rice Residues Through Tillage Enhances Soil Organic Matter Accumulation in Rice Land. - Fiegalan, F. T.
Soil organic matter (SOM) is a critical determinant of the fertility status and productivity of soil, yet SOM status in rice land is degrading. This study was conducted through integrated in situ experimentation (collembola, bacteria, fungi, moisture, temperature, N, P, K) and modeling to determine how to enhance SOM in rice land. An approach to increase SOM by incorporation of rice residues (straw and stubble) through tillage was done. While previous SOM assessment only looked into fine particles (< 0.05 mm, Fn), this study includes both fine and coarse (0.05?2 mm, Lf) SOM fractions. Incorporation of rice residues by tillage increased Lf by 27% (P < 0.001 at 0.05α) while it decreased Fn by 7% (P = .006 at 0.05α). Long-term projection of SOM status generated using system dynamics (SD) modeling showed higher accruals of Lf in the tilled soil due to the physical fragmentation of rice residues. The accumulation of Fn in non-tilled soil was attributed to the synergistic effect of collembola, bacteria, and fungi on the further decomposition of available Lf. Incorporation of 15 T ha?1 yr?1 of rice residues showed accrual of SOM at a rate of 0.03% yr?1. SOM state was observed to decline at ?0.003% yr?1 when rice residue incorporation was reduced to 10 T ha?1 yr?1 with a rate of ?0.003% yr?1, and ?0.04% yr?1 when the residues were further cut down to 5 T ha?1 yr?1. Continuous practice of rice residue incorporation at 20 T ha?1 yr?1 showed tenable SOM accrual and projected to contain > 4.0% within 25 yr. Contrary to previous work, this study showed that incorporating rice residues through tillage enhanced the Lf fraction and, consequently, increased the total SOM.